MODERN TRENDS OF SCHOOL HISTORICAL EDUCATION DEVELOPMENT IN THE REPUBLIC OF KAZAKHSTAN - Seitkaziyev Ruslan; Zhuzey Myrzakhmet; Smankulova Zhanat; Abdugulova Baglan; Kassymov Madiyar; Bissenbayeva Zhanat (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article provides an analysis of the situation in historical science and depicts the modern trends of historical education enhancement at schools of Kazakhstan. This research specifically represents a detailed overview of historical education in modern conditions. Moreover, it is better to focus on the situation that the approaches and conception of historical education undergone different impacts. Actually, the whole research is being made in the stage starting from 1991-2017, but in this research paper we are focusing not particularly on the period but we are giving the general understanding of historical education development in modern science and its necessity to the upbringing of the young generation of our nation. The methodological approaches of the teaching process are presented, and the main tasks to improve the quality of historical education also have been identified during the research.